Language Variation: Perspectives on Lexis and Phraseology - Bondi, Marina; Cacchiani , Silvia (Status Quaestionis, 2024)
This paper provides an overview of the Special Issue. Following an outline of the themes and methodological standpoints discussed in the special issue, it offers an overview of the individual case studies selected for inclusion. While spanning several genres and domains, and discussing lexical and phraseological variation from multiple angles and perspectives, the dominant methodological standpoints in the Special Issue are corpus and discourse analysis. Small and large corpora are used along with lexicographic data to examine key lexical and phraseological questions in language variation, both quantitatively and qualitatively. In particular, special attention is devoted to language choice, linguistic constraints and linguistic innovation as observed in English, Italian, and across English and Italian.